The Impact of Remuneration Policy on Increasing Lecturer’s Motivation and Performance at Universitas Padjadjaran - Rheny Rheny; Rd. Funny Mustikasari Elita; Susie Perbawasari (Universitas Padjadjaran, 2021)
The remuneration policy in the higher education institution is a manifestation of the responsibility of the management leadership in providing awards in the form of additional income with the aim of improving the performance of lecturers. The reform of the lecturer salary payment system became effective in the 2015. This paper attempts to examine the impact of remuneration policies on the motivation and performance of lecturers. This study aims to analyze the positive impact of remuneration policies in an effort to increase the motivation and performance of Padjadjaran University lecturers. This research uses descriptive qualitative method. Research data collection is done through in-depth interview techniques and literature study. Informants in this research are Padjadjaran University management leaders and staffs and Padjadjaran University lecturers. This study uses a three-step data analysis technique, which consists of the process of reducing research data, displaying data and drawing conclusions. The conclusion from this research is that the remuneration policy has a significant impact on efforts to increase the motivation and performance of Padjadjaran University lecturers, with the fulfillment of both intrinsic and extrinsic factors which have a main role in efforts to increase the motivation of lecturers to always try to improve their performance.